2014
DOI: 10.5935/1678-9741.20140045
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Superior Septal Approach with Left Atriotomy in Mitral Valve Surgery

Abstract: Objective In this study, we aimed to compare clinical outcomes of superior transseptal approach with the conventional left atriotomy in patients undergoing mitral valve surgery.Methods Between January 2010 and November 2012, a total of 91 consecutive adult patients (39 males, 52 females; mean age: 54.0±15.4 years; range, 16 to 82 years) who underwent mitral valve surgery in the Division of Cardiovascular Surgery at Koşuyolu Training Hospital were included. The patients were randomized to either superior transs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 18 publications
2
8
1
Order By: Relevance
“…Many authors noted the prolonged CPB time and crossclamp time for MVS with the STS approach. Aydın et al achieved 96.0 min and 83.4 min cross-clamp times with the STS and LA approaches (P = .003) and 128.3 min and 118.3 min CPB times with the STS and LA approaches (P = .02), respectively [Aydin 2014]. Similarly, Masuda et al found a longer cross-clamp time after the STS approach compared with the LA approach; however, they did not give a P value to evaluate the significance of the difference [Masuda 1996].…”
Section: Discussionmentioning
confidence: 99%
“…Many authors noted the prolonged CPB time and crossclamp time for MVS with the STS approach. Aydın et al achieved 96.0 min and 83.4 min cross-clamp times with the STS and LA approaches (P = .003) and 128.3 min and 118.3 min CPB times with the STS and LA approaches (P = .02), respectively [Aydin 2014]. Similarly, Masuda et al found a longer cross-clamp time after the STS approach compared with the LA approach; however, they did not give a P value to evaluate the significance of the difference [Masuda 1996].…”
Section: Discussionmentioning
confidence: 99%
“…However, other reports show that while a superior transseptal approach produces higher postoperative ejection fraction, it does not incur higher risk of arrhythmia compared to a left atriotomy. 6,7 The debate over a transseptal vs a left atrial approach is arguably sustained by the scarcity of data on the types of arrhythmias that arise after MV surgery. Currently, the phenotypes of conduction defects appear to be directly attributable to surgical lesions.…”
Section: Introductionmentioning
confidence: 99%
“…The superior trans‐septal (STS) approach to the mitral valve was first described by Berreklouw et al 2 and Guiraudon et al, 3 and its efficacy in providing good exposure of the mitral valve has been established. The STS approach, however, has been blamed for longer cardiopulmonary bypass and ischemia times, 4,5 increased risk of bleeding, 6 and arrhythmias 7‐10 …”
Section: Introductionmentioning
confidence: 99%